Characteristics of two terbutylazine-degrading bacteria and the construction of a live bacterial agent for effective degradation of terbutylazine in soil - ZHU,JIANGWEI (2022)
Abstract Two kinds of bacteria, named TDJ-7 and TDJ-9, were isolated from the soil, which could degrade terbutylazine effectively. TDJ-7 and TDJ-9 were identified as Bacillus pumilus and Bacillus subtilis. The degradation efficiency of 10mg/L of terbutylazine by TDJ-7 could reach 95% within 6 days, and the strain TDJ-9 could reach 98% under the same conditions. Both strain TDJ-7 and strain TDJ-7 could also effectively degrade simazine, metribuzin, atrazine and ametryn. In addition, strain TDJ-7 and TDJ-9 had been successfully developed into a live bacterial agent that could be used to degrade terbutylazine residue. These results suggest that strain TDJ-7 and TDJ-9 can be used for the bioremediation of terbutylazine or other s-triazine herbicides contamination.